Emotional expressions, but not social context, modulate attention during a discrimination task - Pasqualette, Laura; Kulke, Louisa (Cognition & Emotion, 2024)
Investigating social context effects and emotional modulation of attention in a laboratory setting is challenging. Electroencephalography (EEG) requires a controlled setting to avoid confounds, which goes against the nature of social interaction and emotional processing in real life. To bridge this gap, we developed a new paradigm to investigate the effects of social context and emotional expressions on attention in a laboratory setting. We co-registered eye-tracking and EEG to assess gaze behavior and brain activity while participants performed a discrimination task followed by feedback. Video clips of one second in which a confederate displayed either positive, neutral or negative expressions were presented as feedback to the discrimination task. Participants’ belief was manipulated by telling them that the videos were selected either by the computer (non-social condition) or by the experimenter in the adjacent room that observed them via videochat (social condition). We found that emotional expressions modulated late attention processing in the brain (EPN and LPC), but neither early processing (P1) nor saccade latency. Social context did not influence any of the variables studied. We conclude this new paradigm serves as a stepping stone to the development of new paradigms to study social interaction within EEG experiments.
CRIS-Team Scopus Importer:2024-11-29
Keywords: attention; EEG; emotions; EPN; eye-tracking